2021
DOI: 10.1016/j.csbj.2020.12.028
|View full text |Cite|
|
Sign up to set email alerts
|

Exploiting cheminformatic and machine learning to navigate the available chemical space of potential small molecule inhibitors of SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Again, Kumar A et. al., have used a cheminformatics approach to create different datasets and analyzed scaffold diversity to predict the SARS-CoV-2 inhibitors [49] . Recently, Beck B et al ., used a pre-trained deep learning-based drug-target interaction model called molecule transformer-drug target interaction (MT-DTI) to identify commercially available drugs that could act on SARS-CoV-2 proteins [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Again, Kumar A et. al., have used a cheminformatics approach to create different datasets and analyzed scaffold diversity to predict the SARS-CoV-2 inhibitors [49] . Recently, Beck B et al ., used a pre-trained deep learning-based drug-target interaction model called molecule transformer-drug target interaction (MT-DTI) to identify commercially available drugs that could act on SARS-CoV-2 proteins [50] .…”
Section: Discussionmentioning
confidence: 99%
“…It has appeared only as a candidate SARS-CoV-2 inhibitor in a study that used chemoinformatics and machine learning to detect FDA-approved drugs that could target essential SARS-CoV-2 structures. [17] DISNET data showed a relationship between cefazolin and the SARS-CoV-2-associated-gene, IL2 .…”
Section: Cefazolinmentioning
confidence: 99%
“…More specifically, the DPP-4i sitagliptin has been proposed as a potential treatment for COVID-19 in a couple of computational DR studies. [17] , [54] In addition, it has been reported that diabetic patients treated with the DPP-4i sitagliptin at the time of hospitalization had a lower mortality rate, better clinical outcomes, and more hospital discharges than their diabetic counterparts not taking sitagliptin. [55] …”
Section: Sitagliptin and Vildagliptinmentioning
confidence: 99%
“…Gliptins, especially sitagliptin, reduced the inflammation intensity and may control cytokine storms mostly via nuclear factor kappa B signaling pathway[ 190 , 191 ]. Nevertheless, cheminformatics suggested sitagliptin as anti-severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)[ 192 ] as a result of the expected potential molecular binding between sitagliptin and viral spikes[ 193 ]. Nar et al [ 194 ], showed the ineffectiveness of gliptins against SARS-CoV-2 protease[ 194 ].…”
Section: Dpp-iv Inhibitors (Gliptins)mentioning
confidence: 99%